Developing individualized feedback for listening assessment: Combining standard setting and cognitive diagnostic assessment approaches - Min, Shangchao; He, Lianzhen (Language testing, 2022)
In this study, we present the development of individualized feedback for a large-scale listening assessment by combining standard setting and cognitive diagnostic assessment (CDA) approaches. We used the performance data from 3,358 students’ item-level responses to a field test of a national EFL test primarily intended for tertiary-level EFL learners. The results showed that proficiency classifications and subskill mastery classifications were generally of acceptable reliability, and the two kinds of classifications were in alignment with each other at individual and group levels. The outcome of the study is a set of descriptors that describe each test taker’s ability to understand certain level of oral texts and his or her cognitive performance. The current study, by illustrating the feasibility of combining standard setting and CDA approaches to produce individualized feedback, contributes to the enhancement of score reporting and addresses the long-standing criticism that large-scale language assessments fail to provide individualized feedback to link assessment with instruction.